A integração dos sistemas de armazenamento de energia nos sistemas fotovoltaicos: estudo de caso da gestão da energia na utfpr - Mariano, Juliana D Angela (2021)
Photovoltaic (PV) systems are increasingly present in urban centers, installed in buildings and able of generating their own electrical energy. However, most residential and commercial consumers can present their demand peaks at nighttime, when there is no PV generation. Peak demand can increase costs, causing extra costs for exceeding contracted demand in group A consumers. These problems can be solved with the energy storage systems application, which is already being carried out in some countries. Furthermore, this integration can reduce electricity costs and provide desirable flexibility and reliability for these systems, decreasing renewable energy fluctuations. In this sense, this study aimed to propose energy management strategies through this integration, aiming to improve the demand profile of a university commercial consumer for compensation during peak hours. To achieve the objectives of this research, a pilot project was installed which included a 10 kWp Grid Tie PV System (GTPVS), bidirectional inverters and battery bank, as part of a Research and Development (R&D) project implemented in the Federal University of Technology – Paraná (UTFPR) – Curitiba campus at Neoville headquarters. The methodology consisted of the analysis of variables that interfere with the operation of this system, such as: detailed profile of demand and consumption of the studied location, local energy pricing, PV generation profile, as well as the interaction between PV generator and the energy storage system, and the variation in power fluctuations throughout the year. Additionally, a technical feasibility study was carried out aimed to determine this consumer optimal size through the Homer Grid software. The detailed demand profile allowed to know in depth the peak values were above 80 kW, for school weekdays. Furthermore, the daily analysis of the PV generation profile confirmed that although the PV source is quite variable, the scheduled dispatch operation is not interfered with by the variability and intermittency of the solar source, as the system was designed and programmed to operate in parallel with the electrical network. Regarding the energy consumed at the university, very significant values were obtained, in which the month of July presented the highest consumption for the base year 2019, with a total monthly value of 48,670 kWh. The established operating strategy for the battery bank with a 10% discharge depth resulted in a life cycle of 2500 cycles which can extend its useful life by approximately 9.5 years. The results obtained by the simulation show different levels of energy contribution with percentages of 60.0%, 33.6% and 2.7% respectively.